Hemoglobin Degrading Proteases of Plasmodium falciparum as Antimalarial Drug Targets - Qidwai, Tabish (Current Drug Targets, 2015)
Plasmepsins, falcipains and aminopeptidases are Plasmodium falciparum proteases involved in human host hemoglobin degradation and other processes like erythrocyte invasion and rupture. Antimalarial drug resistance and natural selection in parasite are important reasons that create the urgent need of novel targets and lead compounds to overcome the burden of malaria. This report explored progress of the study covering proteases and their inhibitors specific to hemoglobin degradation. Additionally, in silico predicted antimalarial targets, balancing selection and drug-protein interaction are included.
Keywords: falcipains